MENGURAIKAN NARASI LINGKUNGAN HIDUP DALAM VIDEO MUSIK 'EARTH' MELALUI LENSA TEORI SEMIOTIKA JOHN FISKE - Badar, Muhammad Nail; Yatmikasari, Ika; Nur Sakinah, Myrna (Elite : English and Literature Journal, 2025)
This study explores how environmental messages are constructed and conveyed through the music video Earth by Lil Dicky, analyzed using Fiske’s (1987) semiotic theory. Through the three levels of semiotic analysis namely reality, representation, and ideology, this study explains how verbal and visual signs in the music video work together to form meaningful messages related to environmental issues. Using a qualitative descriptive approach, this study analyzes selected segments of the video that depict environmental problems such as ecological damage and human negligence. The findings reveal that the video utilizes symbolic representations—including animated characters, color schemes, camera angles, and lyrical expressions—to convey themes of conservationism, anthropocentrism, and global collectivism. The song “Earth” serves not only as entertainment but also as a medium to raise awareness about the global environmental crisis and the urgency of collective action. This study contributes to the field of linguistics, particularly semiotic studies, by demonstrating how environmentally themed messages can be communicated through popular media.